The executioner's daughter - Hardstaff, Jane (Carolrhoda Books, a division of Lerner Publishing Group, 2016)
Living with her father in the Tower of London during the reign of King Henry VIII, Moss is disgusted and revolted by both her father's job (executioner) and hers (collecting the freshly severed heads) and wants desperately to escape and find out more about her origins. When she finally finds a way out of the Tower, she discovers the river holds more dangers than she imagined including the Riverwitch's curse. The Riverwitch once helped Moss's family in exchange for a terrible bargain; now she expects Moss to pay the debt.